Profil Symptomatic Voice Problem Pada Terapis Wicara di Rumah Sakit Wilayah Sumatera - Nurgazali .; Anggi Resina Putri; Wiwik Setyaningsih (CV. ITTC INDONESIA, 2025)
This study examines voice problems among speech therapists as professionals who rely on vocal function in clinical practice. The study aims to map the profile of symptomatic voice problems and identify determining factors among speech therapists in Sumatran hospitals. The research design employed a descriptive quantitative approach with a cross-sectional method. The sampling technique applied purposive sampling involving 70 respondents from a total population of 161 therapists. Data collection used the Voice Handicap Index (VHI) questionnaire with descriptive statistical analysis and non-parametric Mann-Whitney and Kruskal-Wallis tests. The findings revealed an average VHI score of 12.86 (SD=10.653) with 91.4% of participants in the no impairment to mild impairment category. Statistical analysis showed no significant correlation between variables of voice use duration, noisy work environment, speaking patterns, throat clearing frequency, and caffeine consumption with VHI scores (p-value > 0.05). However, a trend of increasing VHI scores was observed among therapists working in noisy environments, those with loud speaking habits, and frequent throat clearing. Professional expertise and optimal vocal hygiene practices are suspected to be the main protective factors in maintaining voice health among speech therapists in the Sumatra region. Overall, speech therapists in Sumatran hospitals generally do not experience serious symptomatic voice problems. Professional competence and vocal hygiene implementation are presumed to be dominant protective factors. It is recommended that speech therapists maintain vocal hygiene practices, and that institutions conduct regular voice health training.